Antioxidant Activity, γ-Aminobutyric Acid, and Genome Analysis of Lactiplantibacillus plantarum FL13-2 from Fermented Rice Flour - Songsumanus, Apakorn; Pinyosnit, Natawadee; Kingkaew, Engkarat; Panngeun, Thanapol; Charunanthasunthon, Worasan; Phuengjayaem, Sukanya; Phongsopitanun, Wongsakorn; Tanasupawat, Somboon (Journal of Food Health and Bioenvironmental Science, 2025)
Ten rod-shaped isolates of lactic acid bacteria (LAB) from the traditional fermented rice flour, khao-khab were identified as belonging to the genus Lactobacillus based on phenotypic characteristics. Group I isolates (FL12-1, FL18-1, FL19-1S, FL23-1, FL24-1, FL25-1, and FL26-1) were closely related to Limosilactobacillus fermentum, exhibiting 16S rRNA gene sequence similarity of 99.4%–100%. Group II included FL13-2 and FL22-2 (Group IIA) and FL17B (Group IIB), closely related to Lactiplantibacillus plantarum (99.9%–100%) and Lactiplantibacillus pentosus (100%), respectively. All isolates demonstrated strong antioxidant potential, with 2,2-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity—measured by the standard DPPH assay—ranging from 78.49±1.01% to 91.18±3.95%, surpassing that of ascorbic acid. Strain FL13-2, identified as L. plantarum through genomic analysis (Average Nucleotide Identity (ANI) 98.5%, digital DNA-DNA hybridization (dDDH) 92.5%), produced 2.43 g/L of γ-aminobutyric acid (GABA). It harbored key biosynthesis and transport genes (gadB, gadC, gatABCD, pdxK). Phylogenetic analysis confirmed high sequence similarity of these genes with other LAB strains, supporting their functional roles. The gad system was implicated in acid resistance and GABA production under low pH conditions. Genome annotation revealed bacteriocin genes (Enterocin X β, Plantaricin E, and F) and indicated low pathogenicity and absence of virulence factors. Antimicrobial resistance genes (vanH, vanT, vanY) were detected; however, these are intrinsic to LAB and associated with essential cell wall biosynthesis rather than acquired resistance. Additionally, the presence of the qacJ efflux pump and hlyIII gene—both commonly found in probiotic strains—further supports the safety profile of FL13-2. These findingshighlight L. plantarum FL13-2 as a promising multifunctional probiotic candidate with potent antioxidative, GABA-producing, and antimicrobial properties.